The influence of Teaching at the Right Level (TaRL) approach on grade 1 students’ reading and writing skills in Unggulan Aisyiyah Bantul Elementary School - Erviana, Vera Yuli; Eliza Amalia Istiqomah (Universitas Ahmad Dahlan, 2025)
Teaching at the Right Level (TaRL) is a learning approach that focuses on students' ability levels, not on their grade levels. This study aims to analyze the effectiveness of the TaRL approach in improving the reading and writing skills of grade I students at SD Unggulan Aisyiyah Bantul. The research method used was classroom action research (PTK) with two cycles, which included planning, implementation, observation, and reflection. Data were collected through reading and writing skill tests, classroom observations, and interviews with teachers and students. The results showed that the application of TaRL significantly improved students' reading and writing skills. In the first cycle, there was an increase in understanding letters and syllables, while in the second cycle, most students were able to read and write simple words and sentences more fluently. In addition, students became more confident and motivated in learning as the approach provided developmentally appropriate learning. The findings indicate that the TaRL approach can be an effective strategy for addressing the gap in reading and writing skills at the primary school level. Practically, the results of this study provide recommendations for educators to implement more adaptive and needs-based learning to improve literacy quality. In addition, this approach can also be used as a model in developing education policies that are more inclusive and oriented towards the gradual achievement of basic competencies.